Generation of high-power coherent electromagnetic radiation of nanosecond Length; Radio Engineering and Electronic Physics; Vol. 17, № 7 - Didenko A. N.; Zelentsov V. I.; Shteyn Y. G.; Yushkov Y. G. Yuri Georgievich (1972, 1972)
In this note the results are presented of an experimental investigation of the generation of high-power microwave pulses of nanosecond length when a standing-wave cavity is used to store the microwave energy. The circuit of the device is described